A set of matrices to map the location of profit and economic activity of multinational enterprises - Turban, Sébastien (OECD Publishing, 2020)
This paper describes the methodology and data sources used to build a set of matrices mapping the location of profit and economic activity of multinational enterprises (MNEs) across jurisdictions. These matrices were originally designed for the purpose of assessing the effect of proposals for the reform of international corporate tax arrangements under consideration by the OECD/G20 Inclusive Framework on Base Erosion and Profit Shifting (BEPS). They could also serve other analytical purposes in the future. The set consists of a profit matrix and three matrices focusing on indicators of economic activity (turnover, tangible assets and payroll). Each matrix contains data spanning more than 200 jurisdictions (matrix rows) and broken down across more than 200 jurisdictions of MNE ultimate parent (matrix columns), focusing primarily on year 2016. The matrices combine data from a range of sources in a consistent framework, including newly available aggregated Country-by-Country Report (CbCR) data, the ORBIS database, and the OECD Analytical AMNE database. Gaps in data are filled using extrapolations based on macroeconomic data, including via a sophisticated procedure to extrapolate profit based on foreign direct investment (FDI) data. Extensive benchmarking has been undertaken to ensure consistency across the data sources and extrapolations used in the matrices
Keywords: Finance and Investment; Taxation; Economics